Levamisole modulates the cell-mediated immunity of matrinxã, brycon amazonicus - Biller, Jaqueline Dalbello [UNESP]; Takahashi, Leonardo Susumu [UNESP]; Moromizato, Basia Schlichting [UNESP]; Miasaki, Celso Tadao [UNESP]; Urbinati, Elisabeth Criscuolo [UNESP] (Boletim do Instituto de Pesca, 2019)
The use of immunomodulators is an alternative to improve the immune system of fish and avoid the excessive use of antibiotics. Levamisole is a synthetic anthelmintic which promotes a potent immunostimulation on innate and acquired variables of fish. In order to access the levamisole effects on matrinxã, Brycon amazonicus, fish were fed levamisole at 500 mg kg-1 of diet for seven days. After this period fish were submitted to blood collection. Immunological variables, such as leukocytes respiratory burst, total serum protein, albumin, globulin, albumin:globulin index and hematological variables, such as hematocrit, hemoglobin, red and white blood cell (WBC) and Wintrobe indexes were evaluated. The levamisole administration increased the WBC counts indicating that the immunostimulant modulates the cell-mediated immunity. The increased WBC indicate that the fish fed levamisole were in a better body condition, and probable more resistant to disease due to potential for phagocytosis activation, degranulation of neutrophilic granules, and consequently production of antibodies and immunological memory. Besides, these findings are important for news projects regarding the production of vaccines and deeper understanding of fish cell-mediated immunity.
Levamisole modula a imunidade mediada por células de matrinxã, brycon amazonicus
Keywords: Cellular immunity; Immunostimulant; Innate immunity; White blood cell